2011
DOI: 10.2106/jbjs.j.00760
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Following Intramedullary Nailing of the Femur

Abstract: Patients in our prospective randomized study who were treated with trochanteric nailing did not differ in hip function at one year postoperatively compared with patients treated with intramedullary nailing through the piriformis fossa. The values of several intraoperative parameters were significantly better in the trochanteric nailing group. Our data indicate that the functional hip outcome of femoral intramedullary nailing performed through the greater trochanter is equal to that of intramedullary nailing pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Intramedullary (IM) rods are used as internal fracture fixation devices in long bones, such as the femur and tibia and their first ever use was reported in the 1940s [1]. IM rods are inserted into the medullary canal of the bone to stabilise fracture fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Intramedullary (IM) rods are used as internal fracture fixation devices in long bones, such as the femur and tibia and their first ever use was reported in the 1940s [1]. IM rods are inserted into the medullary canal of the bone to stabilise fracture fragments.…”
Section: Introductionmentioning
confidence: 99%
“…7 performed nailing on fifty-four patients. Out of them 41% had pain and swelling over the fracture site.…”
Section: Resultsmentioning
confidence: 99%
“…However, several papers have also reported significantly more iatrogenic fractures in the GTE group. Stannard et al [3] reported intraoperative parameters including fluoroscopy time and duration of surgery to be better in the GTE group with no differences in functional outcomes. Although some cadaveric studies have claimed that the GT entrance may decrease morbidity due to a reduction in soft tissue injury, [5] other clinical studies have shown that functional outcomes, particularly in regard to the gluteus medius, abductor muscles, and tensor fasciae to be similar between different entrance points [3].…”
Section: Discussionmentioning
confidence: 98%
“…Stannard et al [3] reported intraoperative parameters including fluoroscopy time and duration of surgery to be better in the GTE group with no differences in functional outcomes. Although some cadaveric studies have claimed that the GT entrance may decrease morbidity due to a reduction in soft tissue injury, [5] other clinical studies have shown that functional outcomes, particularly in regard to the gluteus medius, abductor muscles, and tensor fasciae to be similar between different entrance points [3]. However, only a handful of studies have directly compared the effects of the entrance point among supra-isthmal, isthmal, and infra-isthmal femoral shaft fractures [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation